A Novel Helper qPCR Assay for the Detection of miRNA Using Target/Helper Template for Primer Formation - Xianfeng Jiang; Jiahui Wang; Xudan Shen; Jadera Talap; Yang Yang; Dan Yang; Guizhou Xiao; Sheng Cai (International Journal of Analytical Chemistry)
A novel, simple, and sensitive quantitative polymerase chain reaction (qPCR) technology, which is termed as helper qPCR, was established to detect miRNA. In this assay, the target miRNA sequence was introduced as helper template for a reaction switch preforming two-step real-time qPCR strategy. Firstly, the reverse primer was reverse transcribed to form “mediator primer” after binding to the target miRNA. Then, the mediator primer was further extended to form “active template” with annealing to the mediator template. In the end, the active template was amplified and detected by the qPCR reaction system with the help of reverse and forward primers. The SYBR Green dye was used for fluorescence quantification, which is quicker and cheaper than the fluorescent probes, as the detection limit of this assay was 1 pM. This helper qPCR system can be used for different miRNAs detection by redesigning reverse primer for target, indicating this strategy could afford good performance in detecting multiple miRNAs and has a promising application prospect.